2007
DOI: 10.1063/1.2433025
|View full text |Cite
|
Sign up to set email alerts
|

Control of strain status in SiGe thin film by epitaxial growth on Si with buried porous layer

Abstract: Single crystalline Si with buried porous layers was utilized as a substrate for the epitaxy of 100-nm-thick Si0.73Ge0.27. Raman spectroscopy revealed that the strain status in SiGe systematically changes according to the variation in the porosity of the substrate and that the strain relaxation in SiGe was found to proceed with increasing porosity. Furthermore, Si was found to be tensilely strained to reduce the compressive strain in SiGe. These results suggest that the appropriate design of the porosity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…This suggests that the Si 0.73 Ge 0.27 film on the Si (100) wafer was strained. This result agrees with the fact that Si 0.73 Ge 0.27 is strained on a Si wafer, as we previously determined by Raman spectroscopy [24]. Figure 2 shows a cross-sectional HAADF image of Si 0.73 Ge 0.27 /20%-porosity porous Si.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This suggests that the Si 0.73 Ge 0.27 film on the Si (100) wafer was strained. This result agrees with the fact that Si 0.73 Ge 0.27 is strained on a Si wafer, as we previously determined by Raman spectroscopy [24]. Figure 2 shows a cross-sectional HAADF image of Si 0.73 Ge 0.27 /20%-porosity porous Si.…”
Section: Resultssupporting
confidence: 90%
“…It is clear that the origin of the Si 0.73 Ge 0.27 relaxation in this specimen is not the effect of dislocations. The TEM results of this study and the results of our previous analysis by Raman spectroscopy confirmed that the SiGe relaxation is due to the strain of the porous Si layer [24].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations